2020
DOI: 10.1016/j.anai.2020.09.007
|View full text |Cite
|
Sign up to set email alerts
|

Sex effects in the association between airway microbiome and asthma

Abstract: Background: Sex differences exist in asthma susceptibility and severity. Accumulating evidence has linked airway microbiome dysbiosis to asthma, and airway microbial communities have been found to differ by sex. However, whether sex modifies the link between airway microbiome and asthma has not been investigated. Objective: To evaluate sex effects in the association between airway microbiome and asthma. Methods: We analyzed induced sputum samples from 47 subjects (n ¼ 23 patients with asthma and n ¼ 24 normal … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
7
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
1
1

Relationship

2
4

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 39 publications
(49 reference statements)
2
7
0
Order By: Relevance
“…Leptotrichia, Prevotella_7, and Prevotella_2 showed no significant difference between males and females. Furthermore, no difference was found between males and females regarding the Simpson and Shannon indices, indicating a large number of similar strains in males and females, which is consistent with the results reported by Chen et al [ 41 ]. In contrast to our results, when Belstrøm et al used microarrays to examine the oral microbiomes of 292 Danish individuals with low levels of dental caries and periodontitis, they found that diet, BMI, age, and sex did not significantly affect microbial abundance, though socioeconomic status affected the oral microbiome profiles [ 42 ].…”
Section: Discussionsupporting
confidence: 91%
“…Leptotrichia, Prevotella_7, and Prevotella_2 showed no significant difference between males and females. Furthermore, no difference was found between males and females regarding the Simpson and Shannon indices, indicating a large number of similar strains in males and females, which is consistent with the results reported by Chen et al [ 41 ]. In contrast to our results, when Belstrøm et al used microarrays to examine the oral microbiomes of 292 Danish individuals with low levels of dental caries and periodontitis, they found that diet, BMI, age, and sex did not significantly affect microbial abundance, though socioeconomic status affected the oral microbiome profiles [ 42 ].…”
Section: Discussionsupporting
confidence: 91%
“…On the other hand, Lactobacillus in the upper respiratory tract microbiome was significantly associated with mortality in SARS‐CoV‐2‐positive patients 53 . It is worth noting that several studies, including a previous study from our group, have shown associations between increased Lactobacillus in the airway microbiome and respiratory diseases such as asthma and chronic obstructive pulmonary disease, indicating Lactobacillus may not be beneficial when present in the airways 22,54–56 …”
Section: Discussionmentioning
confidence: 91%
“…Before microbial DNA extraction, samples were heated at 56°C for 30 min to inactivate SARS‐CoV‐2 virus. Microbial DNA extraction of saliva and nasopharyngeal swab samples, sequencing library preparation, and 16S rRNA gene sequencing were performed as described previously 22 . Briefly, genomic DNA was extracted from nasopharyngeal swab and saliva samples using the zymoBIOMICS DNA Miniprep Kit (Zymo Research) according to the manufacturer's instructions.…”
Section: Methodsmentioning
confidence: 99%
“…A 16S rRNA gene sequencing analysis of sputum samples from patients with asthma and normal controls found that Haemophilus spp. are associated with asthma in men but not in women [ 40 ]. On the other hand, in contrast to the present study, Raju et al found a high relative abundance of Haemophilus in the saliva microbiota of females [ 41 ].…”
Section: Discussionmentioning
confidence: 99%